Academic medical librarians and video consultations: our new normal. - Brunskill, Amelia; Hanneke, Rosie (Medical Reference Services Quarterly)
Since the onset of the COVID-19 pandemic, interest in video research consultations has rapidly expanded. This study aimed to characterize the current state of academic health sciences librarians' practices and perspectives around this mode of consultation. We distributed a survey, which received 124 eligible responses. Our analysis found that video consultations were now generally in higher demand than in-person consultations and were viewed positively by respondents. Advantages mentioned included convenience & flexibility, technical capabilities, and health benefits. Disadvantages mentioned included technology challenges, issues with engagement, interruptions, and personal preference for in-person meetings.